2013
DOI: 10.3109/0142159x.2013.797570
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the relationship between patient mix and learning in work-based clinical settings. A BEME systematic review: BEME Guide No. 24

Abstract: Background: Clinical workplace-based learning has been the means to becoming a medical professional for many years. The importance of an adequate patient mix, as defined by the number of patients and the types of medical problems, for an optimal learning process is based on educational theory and recognised by national and international accreditation standards. The relationship between patient mix and learning in work-based curricula as yet remains unclear. Aim: To review research addressing the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 59 publications
0
44
0
Order By: Relevance
“…However, the studies included are the most applicable, current evidence on this topic, and the number of studies in our review is consistent with other reviews of issues in medical education. [51][52][53][54] Future directions for this field should include attempts to standardize outcome measures across studies so that there will be more generalizability and studies will be able to be compared more accurately. Additionally, duty hours are only 1 factor in the safety of patients cared for by residents; handover-related communication errors and supervision of residents have also been identified as contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies included are the most applicable, current evidence on this topic, and the number of studies in our review is consistent with other reviews of issues in medical education. [51][52][53][54] Future directions for this field should include attempts to standardize outcome measures across studies so that there will be more generalizability and studies will be able to be compared more accurately. Additionally, duty hours are only 1 factor in the safety of patients cared for by residents; handover-related communication errors and supervision of residents have also been identified as contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is known from medical training that patient mix can impact upon learning in medical students and junior doctors . There were notable differences between the range of services, patient mix and medicines that trainees encountered.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the pharmacy setting, and individuals within it, can have a dramatic impact on an impressionable learner's socialisation into the pharmacy profession as well as propagate the development of a range of professional skills. In other professions, such as medicine, issues relating to individual training sites, such as supervision and patient mix, have been implicated in affecting learning experiences of trainees . These factors shape how learners are supported and exposed to different learning opportunities and disease states and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Although none addressed the issue of students having to recruit their own patients, CCE-Canada and CCE-Australasia limited the proportion of family and/or friends allowed. Case mix has been shown to be positively related to learning outcomes, practitioner reported self-confidence, comfort level and learning benefit in medical education [39]. This suggests that chiropractic students being exposed to a broader case mix, such as hospital settings, could enhance their learning and as such should be considered.…”
Section: Discussionmentioning
confidence: 99%